From the Form to the Meaning (word-formation issues) - HARUTYUNYAN, VERONIKA (Bulletin of Yerevan University H: Russian Philology, 2021)
Thе paper is devoted to the problem of comparative word-formation of the Russian and Armenian languages. It demonstrates some differences between two national language images of the world on the basis of the comparison.